High tide in Hawaii - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series, 2003)
Jack and Annie travel in their Magic Tree House back to a Hawaiian island of long ago where they make friends, learn how to surf, and encounter a tsunami.